Clinical value of free ubiquitin in the identification of diabetic nephropathy in patients with type 2 diabetes mellitus and preliminary exploration of its protective effect - Jing Bian; Jianhui Li; Lina Zhou; Yue Cao; Jinhui Fang (BMC Nephrology)
Abstract Objective Free ubiquitin (Ub) is crucial in various cellular processes. Recent studies suggest that alterations in free Ub levels may be closely associated with the development of diabetes. However, its levels and functional role in diabetic nephropathy (DN) remain unclear. This study investigated the potential of the serum free Ub level as a biomarker for distinguishing DN from non-nephrotic type 2 diabetes mellitus (T2DM) and its underlying mechanisms in DN pathogenesis. Methods The type 2 diabetic nephropathy (T2DN, n = 74) and T2DM (n = 176) patients visited the hospital between September 2021 and September 2023 were retrospectively analyzed, with clinical indicators collected. The correlation between serum free Ub level and renal function indicators [serum uric acid (SUA), blood urea nitrogen (BUN), serum creatinine (Scr), cystatin C (Cys-C), urinary albumin-to-creatinine ratio (UACR), estimated glomerular filtration rate (eGFR)], the independent correlation between serum free Ub expression and T2DN occurrence, and the diagnostic value of serum free Ub expression for early T2DN occurrence in T2DM patients were analyzed by Spearman, Logistic regression, and receiver operating characteristic analyses. The high glucose (HG)-induced renal tubular epithelial cell (HK-2 cell) injury model was treated with different concentrations of free Ub. HK-2 cell viability, proliferation and apoptosis, apoptosis-related protein expression, and interleukin (IL)-6 and IL-1β concentrations were assessed by CCK-8, EdU staining, flow cytometry, western blot and ELISA. Results Compared to the T2DM group, the T2DN group exhibited significantly reduced serum free Ub levels, elevated levels of SUA, BUN, Scr, Cys-C, and UACR, and decreased eGFR levels. Serum free Ub levels in the T2DN group were negatively correlated with SUA, BUN, Scr, Cys-C, and UACR, and positively correlated with eGFR. Serum free Ub was an independent influencing factor and had high diagnostic value for early T2DN occurrence in T2DM patients. After HG (30 mM) treatment, HK-2 cell viability was significantly reduced, cell proliferation was suppressed, and apoptosis was increased, while subsequent free Ub treatment reversed these effects of HG on cell viability, proliferation, and apoptosis. Conclusion Our data suggest that serum free Ub could predict early T2DN occurrence and protect proxìmal tubule cells from HG-induced apoptosis.